Research implications of social network analysis on psychology from 2019 to 2021: a systematic review - Lidia Sandra; Timothy Dillan; Sabar Aritonang (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2022)
This paper aims to give a systematic review on how Social Network Analysis (SNA) Applied in the psychology field of study. Research questions are used to analyse the dataset of journal articles and conference papers collected from IEEE Xplore. 50 papers gathered after applying the advance search of “Social Network Analysis” AND